Emergency department visits for non-urgent conditions in Iran: a cross-sectional study - Bahadori, Mohammadkarim (BMJ Open, 2019)
OBJECTIVES: To determine the percentage of non-urgent (NU) visits in an Iranian emergency department (ED), to explore why patients with NU conditions refer to EDs and also to assess the association between patients’ characteristics and their visits. DESIGN: A cross sectional study based on face to face survey. SETTING: A territorial, teaching and military hospital in Tehran province, Iran. PARTICIPANTS AND DATA COLLECTION: All patients who visited the ED during the 2-week period were recruited. Data were collected using a validated questionnaire. RESULTS: Of 1884 patients who visited the ED, 1217 (64.6%) patients were triaged as NU while 667 (35.4%) were urgent and semiurgent visits cases. The most important reasons for NU visits were seeking prompt (36.6%) and less costly care (35.9%). We found that NU visits have increased with younger patients, during weekends and night shifts, and with patients suffering from recurrent symptoms lasting in 1 week or less. CONCLUSIONS: EDs are a common source of care for NU problems in Iran. The most invaluable solution is building up special clinics for providing healthcare services to NU patients during the weekends and, in the busy and night shifts. Receiving higher fees from NU patients could also be adopted with caution. Promoting awareness and knowledge of both healthcare providers and patients about the main role of EDs will contribute in improving their performance. As a long-term solution, adopting the family physician programme and ameliorating the referral system are recommended.